Tunable Thin Film Periodicities by Controlling the Orientation of Cylindrical Domains in Side Chain Liquid Crystalline Block Copolymers - Lei Dong; Alvin Chandra; Kevin Wylie; Yuta Nabae; Teruaki Hayakawa (International Journal of Polymer Science)
A facile approach to block copolymer (BCP) domain orientation control in thin films has been demonstrated by employing a BCP with liquid crystalline semifluorinated side chains by tuning the composition of the copolymers of the bottom surface layer (BSL). 1H,1H,2H,2H-Perfluorodecanethiol was attached to a precursor polymer, polystyrene-block-poly(glycidyl methacrylate) (PS-b-PGMA), to obtain a novel BCP with a C8F17-containing liquid crystal (LC) side chain (PS-b-P8FMA). Anisotropic hexagonally packed cylinder domains in a bulk state were first characterized by transmission electron microscopy (TEM) and small angle X-ray scattering (SAXS). The observed morphology transition of BCPs with different fluorinated side chain lengths of –CF3, –C4F9, and –C6F13 suggested the decisive effects of LC side chain ordering on the anisotropic nanostructures. In the thin film study, poly(methyl methacrylate-random-2,2,2-trifluoroethyl methacrylate-random-methacrylic acid) (PMMA-ran-PTFEMA-ran-PMAA) solution was used as BSLs for tuning the desired periodicities. The surface free energy (SFE) of BSL was simply tailored by changing the composition of comonomers. In atomic force microscopy (AFM) characterization, long-range ordered perpendicularly oriented BCP domains in a hexagonally packed array or parallel oriented BCP domains as striation patterns were easily fabricated on non-preferential or preferential BSL, respectively. The study presents a novel approach to tunable thin film periodicities without changing or modifying BCPs, which is desired in next-generation BCP lithography.